2017
DOI: 10.1161/circulationaha.117.028561
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase G9a Is Required for Cardiomyocyte Homeostasis and Hypertrophy

Abstract: Taken together, our findings demonstrate that G9a orchestrates critical epigenetic changes in cardiomyocytes in physiological and pathological conditions, thereby providing novel therapeutic avenues for cardiac pathologies associated with dysregulation of these mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 51 publications
0
69
0
Order By: Relevance
“…As a H3K9me3 demethylase, JMJD2A binds to FHL1 promoter and promotes cardiac hypertrophy . By interacting with PRC2, G9a catalyses the formation of H3K9me3, which inhibits the expression of anti‐cardiac hypertrophy genes mediated by the MEF2C complex . In this study, we found that H3K27me2 and H3K36me2 participate in the pathogenesis of ventricular remodelling which is associated with NSD2.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As a H3K9me3 demethylase, JMJD2A binds to FHL1 promoter and promotes cardiac hypertrophy . By interacting with PRC2, G9a catalyses the formation of H3K9me3, which inhibits the expression of anti‐cardiac hypertrophy genes mediated by the MEF2C complex . In this study, we found that H3K27me2 and H3K36me2 participate in the pathogenesis of ventricular remodelling which is associated with NSD2.…”
Section: Discussionmentioning
confidence: 58%
“…HKM plays an important role in the regulation of ventricular remodelling . For example, H3K9me2 and H3K9me3 can inhibit pathological myocardial hypertrophy . NSD2 (The Nuclear SET Domain 2) is one of the major members of the NSD family and is highly expressed in the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…This aberrant DNA methylation was associated with decreased mRNA expression of these two transcription factors, suggesting that DNA methylation plays a key role in transcriptional regulation and pathophysiology of TOF. Similarly, the histone methyltransferase G9a is well‐known to regulate the expression of MEF2C , a transcription factor associated with outflow tract anomalies . While we are learning the importance of transcription factors in the development of CHD, it will be vital to understand the epigenetic regulation of transcription factors.…”
Section: Impact Of Epigenetics In Congenital and Acquired Pediatric Hmentioning
confidence: 99%
“…Similarly, the histone methyltransferase G9a is well-known to regulate the expression of MEF2C, a transcription factor associated with outflow tract anomalies. [23][24][25] While we are learning the importance of transcription factors in the development of CHD, it will be vital to understand the epigenetic regulation of transcription factors.…”
Section: M P a Ct Of E P I Gen E Ti Cs I N Con Ge N It Al A N D Amentioning
confidence: 99%
“…While heart failure is accompanied by two pathological processes, cardiac hypertrophy and cardiac fibrosis, the underlying source results from alterations of gene expression. Cardiac hypertrophy is accompanied by an increase of expression of fetal cardiac genes (e.g., Nppa, Nppb, Myh7 and Skeletal Alpha-Actin) and repression of adult genes (e.g., Myh6), while cardiac fibrosis is a result of an increase of expression of genes encoding proteins of the extracellular matrix (e.g., collagens), processes for which the specific underlying mechanisms still remain unknown [5].…”
Section: Introductionmentioning
confidence: 99%